2010
DOI: 10.1007/s00296-009-1344-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of etanercept and entecavil in a patient with rheumatoid arthritis who is a hepatitis B carrier: a review of the literature

Abstract: In this report, we describe a case of a 48-year-old Japanese woman who is a hepatitis B (HB) carrier with rheumatoid arthritis (RA). She had the following antibody profile: HBs Ag(+), HBs Ab(-), HBe Ag(-), HBe Ab (+), HBc Ab(-) and undetectable HBV-DNA level. She was treated with auranofin, salazosulfapyridine, and bucillamine. Finally, she was treated with D: -penicillamine, but her disease activity remained elevated. Prophylactic treatment of entecavir 0.5 mg daily was started in March 2008 and all disease-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Although specific warnings about hepatitis B reactivation have been added to the US label by the FDA, TNFi have been used in patients with known persistent hepatitis B infection, with concomitant hepatitis B treatment (category B evidence518). If hepatitis B infection is discovered during use of TNFi, prophylactic antiviral treatment can be employed (category C evidence516).…”
Section: Tnf Blocking Agents (Tnfi)mentioning
confidence: 99%
“…Although specific warnings about hepatitis B reactivation have been added to the US label by the FDA, TNFi have been used in patients with known persistent hepatitis B infection, with concomitant hepatitis B treatment (category B evidence518). If hepatitis B infection is discovered during use of TNFi, prophylactic antiviral treatment can be employed (category C evidence516).…”
Section: Tnf Blocking Agents (Tnfi)mentioning
confidence: 99%
“…In particular, rituximab, an anti-CD20 monoclonal antibody used for combined chemotherapy of malignant lymphoma, frequently induces HBV reactivation not only in HBsAg-positive patients, but also in HBsAg-negative patients [6][7][8]. Several studies have reported that infliximab, a monoclonal antibody against tumor necrosis factor-a (anti-TNF-a), induced HBV reactivation in HBsAg-positive patients with Crohn's disease or rheumatoid arthritis (RA) [9][10][11]. Recent case reports showed that HBV reactivation occurred in HBV carriers with RA who received etanercept, adalimumab, or rituximab [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In these particular cases, a multidisciplinary collaboration with a hepatologist is mandatory for the definition of a therapeutic or prophylactic regimen with an antiviral treatment (lamivudine, adefovir, tenofovir, telbivudine, entecavir), as shown by several reports in the literature (2,6,7,10). In our case, due to the severity of psoriasis and the particular psychological patient profile, the risk/benefit ratio led to the decision to start an anti-TNF-a treatment.…”
Section: Discussionmentioning
confidence: 74%
“…Among anti-TNF-a agents etanercept was preferred due to its efficacy and safety profile bound to its biochemical and pharmacological characteristics (soluble TNF-a receptor fusion protein) and for the option to use the drug with intermittent regimens (1,(6)(7)(8)(9). Etanercept was administered in combination with entecavir, an oral deoxyguanosine nucleoside analogue with potent activity against HBV and a high genetic barrier to resistance (10,11), recommended as first-line monotherapy and indicated for long-term use in chronic hepatitis B. Entecavir is administered orally at a dosage of 0.5 or 1 mg/day for a variable period of time depending primarily on HBe or HBs seroconversion. Follow-up visits are usually performed every 3-6 months (10, 11).…”
Section: Discussionmentioning
confidence: 99%